UI/UX Design on the DISPERKIM Lombok Tengah Website Using the Design Thinking Method - Ashari, Maulana; Haerani, Kiki; Zaen, Mohammad Taufan Asri (Journal of Informatics Management and Information Technology, 2024)
DISPERKIM Lombok Tengah is in an effort to improve services to the community by utilizing existing information technology, one of which is using the website. Bad user interface and user experience design from a website will make users uncomfortable and leave the website. However, the current website has not maximized the utilization of user interface and user experience. As for the results of the questionnaire conducted on 30 respondents, 5% felt bad, 43% of respondents felt it was enough, 33% felt it was quite bad, 18% felt it was quite good and 1% felt good, for the appearance and the availability of information on the DISPERKIM Lombok Tengah website right now. The method used in designing UI/UX on the DISPERKIM Lombok Tengah website uses the Design Thinking method. The Design Thinking method has five stages, namely empathize, define, ideate, prototype and test. The wireframe and prototypes are designed by using the Figma application. The Prototype results have passed the testing process to users with good results. So that the proposed design has met the needs of users and can be continued to be implemented. The prototype design is expected to increase interaction satisfaction between the user and the DISPERKIM Lombok Tengah website